ACVA BUILDING STUDIES - STUNTZ, SUSAN (Tufts Archival Research Center, 2007)
Confidential; Memorandum from Susan Stuntz to Walter Woodson regarding an ACVA building study in Oklahoma. States that proper written authorization in advance from the building manager must be received in the future. Suggests that all reports of this particular study be returned.